PARADISE-Parametric Robust Analysis and Design Interactive Software Environment: a Matlab-based robust control toolbox - Sienel, W.; Bunte, T.; Ackermann, J. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
This paper presents a new toolbox for robust control design and analysis. A drawback of physically motivated approaches to robust control has been the amount of extensive calculation required for various methods, e.g. parameter space approach. This new toolbox overcomes these problems and makes parametric robust control methods available in an efficient, easy comprehensible, and flexible manner. The toolbox uses Matlab/Simulink which is a well-know tool to most control engineers.